Distress Factor Analysis of Workers in a Construction Company in 2024 - Safitri, Silvana; Kurniawidjaja, L. Meily (Pusat Publikasi Nusantara, 2024)
This study aims to describe the level of distress and risk factors associated with distress in workers in a construction company, which was conducted in May - December 2024. A cross sectional design was carried out in this study. A total of 255 people who have completed the complete online questionnaire were included in the study. The primary data collection was the measurement of the psychosocial state of workers using a questionnaire distributed online. The measurement of worker stress levels also used DASS 21 and the variables of context of work and context of the work were taken using COPSOQ III, NIOSH questionnaires and previous studies that have gone through validity and reliability tests. A multivariate analysis was conducted to identify the risk factors that have a significant effect on dysstress, namely, marital status and career improvement, status and wages. The dominant risk factors for distress in the construction industry in 2024 are increased careers, status, and wages, with a 95% IK: 1,325 - 5,443, after controlling work schedules/hours, organizational culture and function, and marriage. The findings could serve as a foundation for developing targeted strategies to mitigate distress, enhance workplace conditions, and ultimately improve productivity and morale within construction companies. Furthermore, comparative studies across different construction companies or regions could identify best practices and strategies that successfully reduce distress levels among workers facing similar challenges.